1998
DOI: 10.1063/1.477693
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a combined quantum mechanics/interatomic potential function approach with its periodic quantum-mechanical limit: Proton siting and ammonia adsorption in zeolite chabazite

Abstract: Comparison is made between a combined quantum mechanics/interatomic potential function approach ͑QM-Pot͒ and its fully quantum-mechanical limit, ab initio calculation applying periodic boundary conditions. The Hartree-Fock ͑HF͒ method is combined with ab initio-parametrized ion pair shell model potential functions. The CRYSTAL code is employed for the periodic Hartree-Fock calculations. The same double-/valence triple-zeta polarization basis sets are used in both the approaches. The proton siting and ammonia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 41 publications
6
37
0
Order By: Relevance
“…26,39 and embedded 2T clusters. 44 The corresponding distance for the H 1 proton position in our calculation is longer by 0.025 Å. Greatbanks et al 7 have also found a slight increase of the Al-O͑H͒ and OH distances when embedding a 3T cluster.…”
Section: A Zeolite Cluster Without Adsorbatementioning
confidence: 53%
See 1 more Smart Citation
“…26,39 and embedded 2T clusters. 44 The corresponding distance for the H 1 proton position in our calculation is longer by 0.025 Å. Greatbanks et al 7 have also found a slight increase of the Al-O͑H͒ and OH distances when embedding a 3T cluster.…”
Section: A Zeolite Cluster Without Adsorbatementioning
confidence: 53%
“…Based on periodic calculation Haase et al 26 have found a value of 1196 kJ/mol for the H 1 proton position. Embedding 2T clusters Brändle et al 44 have reported 1277 kJ/mol and 1258 kJ/mol for H 1 and H 3 proton positions, respectively. Compared to our results, the difference in the proton affinity of the two oxygen atoms is larger, 17 kJ/mol, and in their calculations the oxygen atom O 1 has a higher proton affinity than the oxygen atom O 3 .…”
Section: A Zeolite Cluster Without Adsorbatementioning
confidence: 99%
“…In particular, quantum mechanical (QM) simulations have been extensively employed to study concepts in zeolite catalysis, offering a unique way to rationalise experimental results. Simulations of zeolites have ranged from the use of small QM clusters (3T [2,3] & 5T [4,5]), large ring clusters [4][5][6], or more complete representations of the zeolite lattice using ONIOM [4,[7][8][9], QM/MM [10,11] or alternate embedded/periodic methods [9,[12][13][14][15][16]. These references represent a very small sample of those available in the literature and have been highlighted by the author due to the direct relevance to this study.…”
Section: Introductionmentioning
confidence: 99%
“…They accurately describe the reaction center and, at the same time account for structure constraints imposed by, and the long-range interactions with the environment of the site at modest computational expense. 24 We have proposed our own QM-Pot scheme 17,25 and applied it to different problems of zeolite catalysis which involved minima on the potential energy surfaces. 17,[24][25][26][27][28][29][30][31][32] In this work we extend the QM-Pot scheme to studies of transition structures.…”
Section: Introductionmentioning
confidence: 99%